2005
DOI: 10.1111/j.1523-1755.2005.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled trial comparing IV iron sucrose to oral iron in anemic patients with nondialysis-dependent CKD

Abstract: IV iron administration using 1000 mg iron sucrose in divided doses is superior to oral iron therapy in the management of ND-CKD patients with anemia and low iron indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
160
3
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(169 citation statements)
references
References 14 publications
1
160
3
5
Order By: Relevance
“…Compared with baseline, 2 weeks after intravenous Fe, there was an 11-fold increase in serum ferritin and a 2-fold increase in TSAT. However, these changes are not expected to reflect Fe overload, because changes in Fe indicators may take up to 14 days to reach steady state after intravenous Fe (23). At 12 weeks, changes in TSAT and serum ferritin compared with baseline were still significant, although all subjects had TSAT Ͻ50%, and all but one subject had serum ferritin Ͻ500 g/L as recommended by guidelines (4,5).…”
Section: Discussionmentioning
confidence: 92%
“…Compared with baseline, 2 weeks after intravenous Fe, there was an 11-fold increase in serum ferritin and a 2-fold increase in TSAT. However, these changes are not expected to reflect Fe overload, because changes in Fe indicators may take up to 14 days to reach steady state after intravenous Fe (23). At 12 weeks, changes in TSAT and serum ferritin compared with baseline were still significant, although all subjects had TSAT Ͻ50%, and all but one subject had serum ferritin Ͻ500 g/L as recommended by guidelines (4,5).…”
Section: Discussionmentioning
confidence: 92%
“…These data were confirmed by Charytan et al, 48 who showed the safety of IS in hemodialysis patients, including those intolerant of other parenteral iron products. In a randomized, controlled trial comparing IV IS to oral iron in anemic patients with nondialysisdependent CKD, Van Wyck et al 49 showed that IS, given as 1000 mg in divided doses, was more effective than oral iron. In a study of anemic patients with CKD with absent marrow hemosiderin and high serum ferritins, Gotloib et al 50 showed that IV IS administration, with and without ESAs, resulted in increases in hemoglobin levels and achievement of the target hemoglobin of 12 g/dL.…”
Section: Iron Sucrosementioning
confidence: 99%
“…18 The effective use of oral iron therapy may be limited in patients with CKD due to insufficient intestinal absorption and gastrointestinal complaints that may reduce patient compliance with treatment. 22 Three of the four published randomized controlled trials that examined the efficacy of treatment with IV and oral iron in anemic, ND-CKD patients indicated that IV iron was more efficacious than oral iron, 23,24,25 whereas a fourth showed no added benefit from IV iron. 26 Taken together, these studies A n estimated 26 million adults in the United States have chronic kidney disease (CKD).…”
Section: Methods: This Was a Retrospective Cohort Analysis Using 2006mentioning
confidence: 99%